Aluminum prevents stomatal conductance from responding to vapor pressure deficit in Citrus limonia - Silva, Giselle Schwab [UNESP]; Gavassi, Marina Alves [UNESP]; Nogueira, Matheus Armelin [UNESP]; Habermann, Gustavo [UNESP] (Elsevier, 2018)
Stomatal aperture generally increases in response to low vapor pressure deficit (VPD) and decreases at high VPD. Aluminum (Al) inhibits root growth, indirectly exposing the roots to low water availability, which may decrease leaf hydration and, consequently, the stomatal conductance (gs). In this study, Citrus limonia (‘Rangpur’ lime) was grown in nutrient solution with 1480 μM Al for 90 days, and we expected that the presence of Al could prevent gs from responding to VPD. As expected, gs did not respond to the increase in VPD in plants exposed to Al. Aluminum also reduced the relative water content and midday leaf water potential (Ψmd) after 60 and 90 days. The CO2 assimilation rate (A) followed the same response pattern exhibited by gs, the estimation of the carboxylation efficiency was not reduced in plants exposed to Al and measured under drier air, while photochemical responses were slightly reduced in plants exposed to Al, indicating that the Al-induced decrease in A was dependent on gs and less ascribed to low photochemical performance. Like in drought conditions, the long-term exposure to Al reduces leaf hydration and compromises gs responses to the atmosphere, eventually impairing A in ‘Rangpur’ lime plants.
Keywords: Indirect Al effect; Leaf gas exchange; Leaf hydration; ‘Rangpur’ lime